The differential phase pattern of the CSU CHILL radar antenna - Chandrasekar, V., author; Mudukutore, A., author; Mueller, E. A., author; American Meteorological Society, publisher (Colorado State University. Libraries, 1995)
The measurement of the differential propagation phase and copolar correlation coefficient are affected by the differential phase pattern of the antenna system when operating in an alternate horizontal and vertical transmitting scheme. Direct phase pattern measurements of a large dish such as that of the CSU CHILL is difficult because of the need to obtain phase reference. A simple technique is devised to measure the differential phase pattern of the CSU CHILL antenna system. The measurements are subsequently used in the evaluation of the antenna imposed limit on the copolar correlation coefficient.